Pelatihan Branding dan Promosi Digital Sebagai Strategi Peningkatan Daya Saing Pelaku Usaha UMKM Konawe Selatan - Harjun Harjun; Muh Fathul Ikrar; Yasmin Saul Sambolayuk; Asriyani Mulia Basri; Rizal Rizal; Abdullah Igo BD; Hasniah Hasniah; Murni Nia; Ramly Ramly; Wa Ode Fazri Samsinar (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program was themed "Branding and Digital Promotion Training as a Strategy to Increase the Competitiveness of MSMEs in South Konawe." The training targeted sixteen (16) MSMEs, both in the same and different business types, who were expected to be able to develop their businesses after participating in the training. Digital marketing training for MSMEs in South Konawe positively contributed to increasing the knowledge, skills, and awareness of entrepreneurs in utilizing digital technology as a marketing strategy. Through a combination of material delivery and practice, participants mastered product photography techniques, digital catalog management, promotional content creation, branding strategies, social media utilization, and marketplace management, enabling them to build a more professional business identity and expand market reach. Therefore, this training is a strategic step in encouraging the digital transformation of MSMEs, increasing their competitiveness, and supporting the sustainable improvement of MSME welfare and the regional economy.